Mesoporous Silicon: Short and Long Term, In Vitro and In Vivo Correlations of Cellular and Tissue Responses to Mesoporous Silicon Nanovectors (Small 9–10/2013). Issue 9 (16th May 2013) - Martinez, Jonathan O.; Boada, Christian; Yazdi, Iman K.; Evangelopoulos, Michael; Brown, Brandon S.; Liu, Xuewu; Ferrari, Mauro; Tasciotti, Ennio
<x xml:space="preserve">Abstract</x> Current assessment of the toxicity associated with nanocarriers provides poor insight into their true impact on cell function and cell fate. This pseudo‐colored scanning electron microscopy image from E. Tasciotti and co‐workers shows a nanoporous silicon particle in the process of being engulfed by murine macrophages. The particle induces a response in the macrophage, which triggers filopodic tentacles to extend and capture the nanocarrier to begin phagocytosis. Alternative methods are proposed on page 1722 to effectively study the influences of nanovectors on biological systems. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>